Comparison between telestroke versus face-to-face thrombolysis models in stroke management in Colombia (2023)
Introduction: The incidence of stroke continues to rise globally, as it remains an important cause in overall mortality and disability. Given the fact that several patients cannot access thrombolytic therapy due to neurologist unavailability or because of geographic barriers, Teleictus and Telestroke have become reasonable alternatives for providing treatment. Objective: The Teleictus network in Colombia was first implemented in 2018 in Boyacá; Our main goal was to compare the results of two models approaching patient care in stroke: Telestroke versus Face-to-face thrombolysis. Materials and Methods: This was an observational, analytic study using a retrospective cohort. Sociodemographic, clinical, protocol thrombolysis related and clinical evolution variables were considered into the study. Results 65 patients were allocated to the Face-to-face thrombolysis model and 35 were set into the Telestroke model. Median age was 69 and 67 years respectively; both groups had a higher proportion of women than men. Median symptom-onset-to-door time was 136 min in the Face-to-face thrombolysis and 81 min in the Telestroke model p = 0.0083. Median start NIHSS was eleven points for the former and twelve for the latter. At discharge, both groups had a median NIHSS score of 4. Conclusions: Thrombolytic therapy showed safety and efficacy. First and second level institutions are key in the setup of the Telestroke and Teleictus algorithms. More studies are needed to further evaluate this intervention.